Heat-conducting gasket with low oil permeability and low volatility and preparation method of heat-conducting gasket
The thermal pad is solved by cross-linking reactions using low hydrogen-containing methyl terminal methyl hydrogen siloxane and high viscosity polydimethyl siloxane in the thermal gasket and using surface-modified thermal fillers The oil seepage and silane migration problems during use of the sheet achieve excellent thermal conductivity and long-term stability.
Patent Information
- Application Number
- CN202411783993.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-11
AI Technical Summary
During use, existing thermal gaskets have problems such as oil leakage and silane migration, which leads to a decrease in thermal conductivity and mechanical properties, and contaminate the circuit of electronic components, affecting their performance and life.
Cross-linking reactions are carried out using methyl-terminated methylhydrogen siloxane with low hydrogen and high viscosity polydimethylsiloxane to reduce the low molecular by-products generated in the cross-linking reaction and heat conduction through surface modification Fillers improve the dispersion and thermal conductivity of fillers.
It significantly reduces the oil seepage and silane migration of the material, improves the thermal conductivity and structural strength of the thermal gasket, extends its service life, and reduces contamination of electronic components.
Smart Images

Figure CN119410157A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of thermal conductive materials, and in particular to a thermal conductive gasket with low oil permeability and low volatility and a preparation method thereof. Background Art
[0002] As electronic devices continue to become smaller, more integrated, and more powerful, the heating problem of devices is becoming increasingly serious. In order to ensure that electronic components can dissipate heat efficiently and maintain long-term stable operation, the importance of thermal conductive materials in thermal management systems is increasing.
[0003] Thermally conductive pads are a key thermal interface material, usually composed of a silicone oil matrix (such as vinyl silicone oil, hydrogen-terminated silicone oil, hydrogenated silicone oil, etc.), thermally conductive fillers (such as aluminum oxide, boron nitride, magnesium oxide, etc.), catalysts and inhibitors. Thermally conductive pads have good thermal conductivity, electrical insulation and mechanical flexibility. They can fill the interface gap between the heating element and the heat sink, eliminate the unevenness of the microscopic rough surface, thereby reducing the interface thermal resistance and improving the heat transfer efficiency.
[0004] Although existing thermal pads have greatly improved the heat dissipation performance of electronic devices, there are still problems such as material oil seepage and silane migration in actual applications. Long-term use will cause the thermal conductivity and mechanical properties to deteriorate, and pollute the circuits of electronic components, affecting the performance and life of electronic components. Summary of the invention
[0005] In view of the above-mentioned problems, the present application is proposed to provide a low-penetration and low-volatile thermal conductive pad and a preparation method thereof that overcomes the problems or at least partially solves the problems, including:
[0006] A low-penetration and low-volatility thermally conductive pad, comprising the following raw materials by weight: 2-8 parts of low-end vinyl-free polydimethylsiloxane, 0.1-3 parts of low-end methyl-free end-capped methylhydrogensiloxane, 1-5 parts of polydimethylsiloxane, 90-96 parts of modified thermally conductive filler, 0.1-1 parts of platinum catalyst and 0.1-1 parts of inhibitor;
[0007] The low-end vinyl-free polydimethylsiloxane and the low-end methyl-free terminated methylhydrogensilane are obtained by distillation and purification of vinyl-terminated polydimethylsiloxane and methyl-terminated methylhydrogensilane, respectively; the viscosity of the vinyl-terminated polydimethylsiloxane is 450-2100 mPa·s, and the vinyl content is 0.2-0.45 wt %; the hydrogen content of the methyl-terminated methylhydrogensiloxane is 0.04-0.15 wt %; and the viscosity of the methyl silicone oil is 100000-500000 mPa·s.
[0008] Preferably, the content of small molecule substances in the low-end vinyl-free polydimethylsiloxane is less than 0.1 wt %; wherein the molecular weight of the small molecule substances is less than 500 Da.
[0009] Preferably, the content of small molecule substances in the de-low-methyl terminated methyl hydrogen siloxane is less than 0.1 wt %; wherein the molecular weight of the small molecule substances is less than 500 Da.
[0010] Preferably, the modified thermally conductive filler comprises the following raw materials in parts by mass: 98-99.8 parts of thermally conductive filler and 0.2-2 parts of treating agent.
[0011] Preferably, the thermally conductive filler includes at least one of aluminum oxide, aluminum nitride, aluminum hydroxide, zinc oxide and diamond.
[0012] Preferably, the treating agent includes at least one of y-(2,3-epoxypropoxy)propyltrimethoxysilane, y-methacryloxypropyltrimethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, single-end trimethyl / ethoxysilane-terminated polydimethylsiloxane and polyether-modified polydimethylsiloxane.
[0013] Preferably, the treating agent includes at least one of y-(2,3-epoxypropoxy)propyltrimethoxysilane, y-methacryloxypropyltrimethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, and single-end trimethyl / ethoxysilane-terminated polydimethylsiloxane and polyether-modified polydimethylsiloxane.
[0014] A method for preparing a thermally conductive gasket as described in any one of the above items, comprising:
[0015] The modified thermal conductive filler, the low-end vinyl-free polydimethylsiloxane, the low-end methyl-free methyl hydrogen siloxane, the polydimethylsiloxane, the platinum catalyst and the inhibitor are mixed and stirred according to the proportion, and vacuum degassing treatment is performed to obtain a thermal conductive colloid;
[0016] The thermally conductive colloid is subjected to calendering and vulcanization treatment to obtain a thermally conductive gasket.
[0017] Preferably, it also includes:
[0018] The thermal conductive filler and the treating agent are stirred and mixed according to a proportion to obtain a modified thermal conductive filler.
[0019] Preferably, it also includes:
[0020] The vinyl-terminated polydimethylsiloxane and the methyl-terminated methylhydrogensiloxane were distilled at 180° C. for 2 h to obtain the low-vinyl-terminated polydimethylsiloxane and the low-methyl-terminated methylhydrogensiloxane.
[0021] This application has the following advantages:
[0022] In view of the problems of oil seepage and silane migration in existing thermal conductive gasket materials, the present application provides a solution that uses low-hydrogen-containing methyl-terminated methyl hydrogen siloxane to reduce the low molecular byproducts generated by the cross-linking reaction and is matched with high-viscosity polydimethylsiloxane to ensure structural strength while improving the cross-linking support strength, thereby reducing material oil seepage and silane migration. Specifically, a low-oil seepage and low-volatility thermal conductive gasket comprises the following raw materials by mass: 2-8 parts of low-end vinyl polydimethylsiloxane, 0.1-3 parts of low-methyl-terminated methyl hydrogen siloxane, 1-5 parts of polydimethylsiloxane, and 90 parts of modified thermal conductive filler. -96 parts, 0.1-1 parts of platinum catalyst and 0.1-1 parts of inhibitor; wherein the low-end vinyl-free polydimethylsiloxane and the low-methyl-free terminated methylhydrogensilane are obtained by distillation and purification of vinyl-terminated polydimethylsiloxane and methyl-terminated methylhydrogensilane respectively; the viscosity of the vinyl-terminated polydimethylsiloxane is 450-2100mPa·s, and the vinyl content is 0.2-0.45wt%; the hydrogen content of the methyl-terminated methylhydrogensiloxane is 0.04-0.15wt%; the viscosity of the methyl silicone oil is 100000-500000mPa·s.
[0023] By adopting de-low-polymerized vinyl-terminated polydimethylsiloxane and methyl-terminated methylhydrogensiloxane, the small molecular substances in the matrix material can be significantly reduced, and the volatile components in the matrix material can be reduced; by adopting methyl-terminated methylhydrogensiloxane with a hydrogen content of 0.04-0.15wt% and vinyl-terminated polydimethylsiloxane with a viscosity of 450-2100mPa·s and a vinyl content of 0.2-0.45wt% for cross-linking reaction, the low molecular by-products generated in the cross-linking reaction can be significantly reduced, and the volatile components in the matrix material can be further reduced. When used with polydimethylsiloxane with a viscosity of 100000-500000mPa·s, sufficient structural strength can be ensured while improving the cross-linking support strength, thereby effectively reducing material oil seepage and silane migration; in addition, by adopting surface-modified thermally conductive fillers, the dispersibility of the fillers in the high-viscosity silicone oil matrix can be improved, thereby ensuring the filling amount of the thermally conductive fillers to achieve excellent thermal conductivity.
[0024] The thermally conductive gasket provided in the present application has excellent thermal conductivity, low oil seepage and low volatility. Its thermal conductivity coefficient is as high as 4 to 8 W / m·K, which can effectively improve the heat dissipation efficiency of electronic components. At the same time, the oil seepage diameter is reduced from 48 mm to below 22 mm, and the siloxane content is reduced from more than 1000 ppm to less than 200 ppm, which can effectively reduce the pollution of electronic components caused by oil seepage and volatilization. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solution of the present application, the drawings required for use in the description of the present application will be briefly introduced below. Obviously, the drawings described below are only part of the embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0026] Figure 1 It is a flowchart of the steps of the first part of the method for preparing a thermally conductive gasket provided in one embodiment of the present application;
[0027] Figure 2 It is a flow chart of the steps of the second part of the method for preparing a thermally conductive gasket provided in one embodiment of the present application;
[0028] Figure 3 It is a flow chart of the steps of the third part of the method for preparing a thermally conductive gasket provided in one embodiment of the present application;
[0029] Figure 4 These are actual photos of the oil seepage diameter detection results of Examples 1-3 and Comparative Example 1. DETAILED DESCRIPTION
[0030] In order to make the purpose, features and advantages of the present application more obvious and easy to understand, the present application is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
[0031] The inventors have found through analysis of the prior art that the cross-linking reaction materials (such as hydrogen-terminated silicone oil, etc.) used in the existing thermal pads contain silicon-hydrogen bonds (Si-H) groups at multiple active sites, and it is easy to generate more volatile low-molecular byproducts during the reaction process, which will cause problems such as material oil seepage and silane migration. In addition, in order to improve the thermal conductivity, a large amount of thermal conductive fillers need to be filled into the silicone oil matrix, and silicone oil with lower viscosity is often used to ensure the dispersibility of the filler, thereby reducing the overall cross-linking degree, and also causing problems such as material oil seepage and silane migration. Long-term use will pollute the circuits of electronic components and affect the performance and life of electronic components. The silicone oil matrix usually contains a certain amount of small molecules, which are very volatile under high-temperature conditions. The loss of volatile components will destroy the structural integrity of the thermal pad, reduce the interface filling performance, and condense on the surface of the electronic component after volatilization, which will also form pollution, resulting in component performance degradation or failure. In addition, since the thermal conductive filler has a large specific surface area and strong intermolecular forces, it is easy to agglomerate in the system. This agglomeration will hinder the full reaction between the treatment agent and the hydroxyl groups on the surface of the filler, further causing excess treatment agent to seep out, affecting the long-term stability of the thermal conductive gasket and possibly contaminating electronic components.
[0032] In one embodiment of the present application, a low-penetration and low-volatile thermally conductive pad is provided, which includes the following raw materials by mass: 2-8 parts of de-low-end vinyl polydimethylsiloxane, 0.1-3 parts of de-low-methyl end-capped methyl hydrogen siloxane, 1-5 parts of polydimethylsiloxane, 90-96 parts of modified thermally conductive filler, 0.1-1 parts of platinum catalyst and 0.1-1 parts of inhibitor;
[0033] The low-end vinyl-free polydimethylsiloxane and the low-end methyl-free terminated methylhydrogensilane are obtained by distillation and purification of vinyl-terminated polydimethylsiloxane and methyl-terminated methylhydrogensilane, respectively; the viscosity of the vinyl-terminated polydimethylsiloxane is 450-2100 mPa·s, and the vinyl content is 0.2-0.45 wt %; the hydrogen content of the methyl-terminated methylhydrogensiloxane is 0.04-0.15 wt %; and the viscosity of the methyl silicone oil is 100000-500000 mPa·s.
[0034] As an example, the vinyl-terminated polydimethylsiloxane includes at least one of a vinyl-terminated polydimethylsiloxane having a viscosity of 1900-2100 mPa·s and a vinyl content of 0.2-0.24 wt%, a vinyl-terminated polydimethylsiloxane having a viscosity of 450-550 mPa·s and a vinyl content of 0.4-0.45 wt%, and a vinyl-terminated polydimethylsiloxane having a viscosity of 950-1100 mPa·s and a vinyl content of 0.3-0.34 wt%.
[0035] As an example, the methyl-terminated methyl hydrogen siloxane includes at least one of methyl-terminated methyl hydrogen siloxanes having a hydrogen content of 0.04-0.06 wt %, 0.09-0.11 wt %, and 0.13-0.15 wt %.
[0036] As an example, the methyl silicone oil includes at least one of methyl silicone oils having a viscosity of 100,000 mPa·s, a viscosity of 200,000 mPa·s, and a viscosity of 500,000 mPa·s.
[0037] By adopting de-low-polymerized vinyl-terminated polydimethylsiloxane and methyl-terminated methylhydrogensiloxane, the small molecular substances in the matrix material can be significantly reduced, and the volatile components in the matrix material can be reduced; by adopting methyl-terminated methylhydrogensiloxane with a hydrogen content of 0.04-0.15wt% and vinyl-terminated polydimethylsiloxane with a viscosity of 450-2100mPa·s and a vinyl content of 0.2-0.45wt% for cross-linking reaction, the low molecular by-products generated in the cross-linking reaction can be significantly reduced, and the volatile components in the matrix material can be further reduced. When used with polydimethylsiloxane with a viscosity of 100000-500000mPa·s, sufficient structural strength can be ensured while improving the cross-linking support strength, thereby effectively reducing material oil seepage and silane migration; in addition, by adopting surface-modified thermally conductive fillers, the dispersibility of the fillers in the high-viscosity silicone oil matrix can be improved, thereby ensuring the filling amount of the thermally conductive fillers to achieve excellent thermal conductivity.
[0038] The thermally conductive gasket provided in this embodiment has excellent thermal conductivity, low oil seepage and low volatility, and its thermal conductivity is as high as 4 to 8 W / m·K, which can effectively improve the heat dissipation efficiency of electronic components. At the same time, the oil seepage diameter is reduced from 48 mm to below 22 mm, and the siloxane content is reduced from more than 1000 ppm to less than 200 ppm, which can effectively reduce the pollution of electronic components caused by oil seepage and volatilization.
[0039] Next, the thermally conductive pad in this exemplary embodiment will be further described.
[0040] In one embodiment of the present application, the content of small molecule substances in the low-end vinyl-free polydimethylsiloxane is less than 0.1 wt %; wherein the molecular weight of the small molecule substances is less than 500 Da.
[0041] In one embodiment of the present application, the content of small molecule substances in the de-low-methyl terminated methyl hydrogen siloxane is less than 0.1 wt %; wherein the molecular weight of the small molecule substances is less than 500 Da.
[0042] In one embodiment of the present application, the modified thermally conductive filler comprises the following raw materials by weight: 98-99.8 parts of thermally conductive filler and 0.2-2 parts of treating agent. The modified thermally conductive filler is obtained by surface modification of the thermally conductive filler. The surface treatment of the treating agent can ensure that the thermally conductive filler is evenly dispersed to avoid agglomeration or sedimentation.
[0043] In one embodiment of the present application, the thermally conductive filler is pre-dispersed. By pre-dispersing the thermally conductive filler, the agglomeration formed by the intermolecular force between the thermally conductive fillers can be broken, which helps the filler to better react with the treatment agent and disperse in the silicone oil matrix, while preventing excess unreacted treatment agent from leaking out and contaminating the equipment.
[0044] In one embodiment of the present application, the thermally conductive filler includes at least one of aluminum oxide, aluminum nitride, aluminum hydroxide, zinc oxide and diamond. The above-mentioned thermally conductive fillers have good thermal conductivity, electrical insulation and chemical stability.
[0045] In one embodiment of the present application, the treating agent includes at least one of y-(2,3-epoxypropoxy)propyltrimethoxysilane, y-methacryloxypropyltrimethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, single-ended trimethyl / ethoxysilane-terminated polydimethylsiloxane and polyether-modified polydimethylsiloxane.
[0046] In a preferred embodiment of the present application, the treatment agent includes at least one of y-(2,3-epoxypropoxy)propyl trimethoxysilane, y-methacryloxypropyl trimethoxysilane, dodecyl trimethoxy silicone oil, dodecyl triethoxysilane, hexadecyl trimethoxysilane, and hexadecyl triethoxysilane, and at least one of single-terminal trimethyl / ethoxysilane-terminated polydimethyl silicone oil and polyether-modified polydimethylsiloxane. It should be noted that the molecular weight of y-(2,3-epoxypropoxy)propyl trimethoxysilane, y-methacryloxypropyl trimethoxysilane, dodecyl trimethoxy silicone oil, dodecyl triethoxysilane, hexadecyl trimethoxysilane, and hexadecyl triethoxysilane is relatively low, while the molecular weight of single-terminal trimethyl / ethoxysilane-terminated polydimethyl silicone oil and polyether-modified polydimethylsiloxane is relatively high. By combining treatment agents with different molecular weights, a layer of steric hindrance can be formed on the surface of the thermally conductive filler to avoid direct contact between the fillers, thereby effectively weakening the aggregation effect between the fillers.
[0047] In a preferred embodiment of the present application, the treating agent includes at least one of y-(2,3-epoxypropoxy)propyltrimethoxysilane and y-methacryloxypropyltrimethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, at least one of single-end trimethyl / ethoxysilane-terminated polydimethylsiloxane and polyether-modified polydimethylsiloxane, and at least one of single-end trimethyl / ethoxysilane-terminated polydimethylsiloxane and polyether-modified polydimethylsiloxane. It should be noted that y-(2,3-epoxypropoxy)propyl trimethoxysilane and y-methacryloxypropyl trimethoxysilane can eliminate the hydroxyl groups on the surface of the filler through chemical reactions, thereby reducing agglomeration; long-chain alkyl groups such as dodecyl trimethoxy silicone oil, dodecyl triethoxysilane, hexadecyl trimethoxysilane and hexadecyl triethoxysilane can increase the hydrophobicity of the filler and enhance the interfacial bonding between the filler and the silicone oil matrix; high molecular weight compounds such as single-end trimethyl / ethoxysilane-terminated polydimethyl silicone oil and polyether-modified polydimethylsiloxane can increase lubricity and polar compatibility, and improve the dispersion stability of the filler in the polar matrix. By matching different types and molecular weights of treatment agents, the hydroxyl groups on the surface of the thermal conductive filler can be eliminated to reduce the adsorption tendency between particles, and the surface chemical properties of the thermal conductive filler can be improved to enhance its interfacial bonding with the matrix material. At the same time, a layer of steric hindrance can be formed on the surface of the thermal conductive filler to effectively weaken the aggregation between the fillers, thereby ensuring that the thermal conductive filler is evenly dispersed and avoiding agglomeration or sedimentation.
[0048] In one embodiment of the present application, the inhibitor includes at least one of a polyvinyl small molecule and ethynyl cyclohexanol. By introducing a polyvinyl small molecule or ethynyl cyclohexanol inhibitor, the rate of the crosslinking reaction can be effectively regulated to ensure sufficient operating time.
[0049] Reference Figure 1 In one embodiment of the present application, a method for preparing a thermally conductive gasket as described in any of the above embodiments is provided, comprising:
[0050] S110, mixing the modified thermally conductive filler, the low-end vinyl-free polydimethylsiloxane, the low-end methyl-free methyl hydrogen siloxane, the polydimethylsiloxane, the platinum catalyst and the inhibitor according to a proportion, and performing a vacuum degassing treatment to obtain a thermally conductive colloid;
[0051] S120, performing calendering and vulcanization treatment on the thermally conductive colloid to obtain a thermally conductive gasket.
[0052] Next, the preparation method of the potting compound in this exemplary embodiment will be further described.
[0053] As described in step S110, the modified thermally conductive filler, low-end vinyl-free polydimethylsiloxane, low-end methyl-free methyl hydrogen siloxane, polydimethylsiloxane, platinum catalyst and inhibitor are stirred and mixed according to the proportion, and vacuum degassing treatment is performed to obtain a thermally conductive colloid.
[0054] The modified thermal conductive filler, low-end vinyl polydimethylsiloxane, low-methyl end-capped methylhydrogensiloxane, polydimethylsiloxane, platinum catalyst and inhibitor are put into a reaction kettle according to the proportion, dispersed evenly by a planetary mixer (stirring rate is 15-40Hz, stirring time is 2h), and vacuum degassing is performed after mixing (degassing time is 10 to 15min, vacuum degassing pressure is -0.095 to -0.1MPa) to obtain a thermal conductive colloid.
[0055] As described in step S120, the thermally conductive colloid is subjected to calendering and vulcanization treatment to obtain a thermally conductive gasket.
[0056] The thermal conductive colloid is put into a calender, the corresponding thickness is set, and after calendering, it passes through a vulcanization tunnel (the vulcanization temperature is 140-150°C, and the vulcanization time is 10-20 minutes), and a thermal conductive gasket is obtained after vulcanization.
[0057] Reference Figure 2 In one embodiment of the present application, the method further includes:
[0058] S010, stirring and mixing the thermal conductive filler and the treating agent according to a proportion to obtain a modified thermal conductive filler.
[0059] The thermal conductive filler is put into a high-speed mixer according to the ratio, and first dispersed and mixed (the equipment speed is 10-40Hz, the time is 1-5min), and then the treatment agent is added, and then high-speed dispersed and mixed (the equipment speed is 10-40Hz, the time is 3-10min) to obtain a modified thermal conductive filler.
[0060] Reference Figure 3 In one embodiment of the present application, the method further includes:
[0061] S020, distill the vinyl-terminated polydimethylsiloxane and the methyl-terminated methylhydrogensiloxane at 180° C. for 2 h to obtain the low-vinyl-free polydimethylsiloxane and the low-methyl-free methylhydrogensiloxane.
[0062] The vinyl-terminated polydimethylsiloxane and the methyl-terminated methylhydrogensiloxane were respectively placed in a distillation tower and decomposed at a high temperature of 180° C. for 2 hours to obtain low-vinyl-terminated polydimethylsiloxane and low-methyl-terminated methylhydrogensiloxane.
[0063] The specific embodiments and experimental data of this application are as follows:
[0064] Embodiment 1
[0065] A low-penetration and low-volatile thermally conductive pad, comprising the following raw materials by weight: 4.3 parts of de-low-end vinyl polydimethylsiloxane, 0.7 parts of de-low-methyl end-capped methylhydrogensilane, 1 part of 500,000 mPa·s polydimethylsiloxane, 0.1 parts of platinum catalyst, 0.2 parts of inhibitor, and 93.6 parts of modified thermally conductive filler;
[0066] The modified thermal conductive filler includes the following raw materials by mass: 40 parts of 70 μm spherical alumina, 10 parts of 40 μm alumina, 35 parts of 5 μm spherical alumina, 10 parts of 3 μm quasi-spherical alumina, 4.5 parts of 1 μm zinc oxide, 0.2 parts of dodecyl trimethoxysiloxane, and 0.3 parts of single-end trimethoxysilane-terminated polydimethylsilicone oil;
[0067] The low-end vinyl-free polydimethylsiloxane and the low-end methyl-free methyl-terminated methylhydrogensilane are purified at 180°C from vinyl-terminated polydimethylsiloxane with a viscosity of 1900-2100 mPa·s and a vinyl content of 0.2-0.24 wt% and methyl-terminated methylhydrogensilane with a hydrogen content of 0.04-0.06 wt%.
[0068] The preparation method of the thermally conductive pad comprises:
[0069] By mass, 40 parts of 70 μm spherical alumina, 10 parts of 40 μm alumina, 35 parts of 5 μm spherical alumina, 10 parts of 3 μm quasi-spherical alumina, and 4.5 parts of 1 μm zinc oxide were put into a high-speed mixer for mixing (the equipment speed was 10 Hz, and the time was 1 min), 0.2 parts of dodecyl trimethoxysiloxane and 0.3 parts of single-end trimethoxysilane-terminated polydimethylsilicone were added, and then dispersed and mixed at a high speed (the equipment speed was 25 Hz, and the time was 5 min) to obtain a modified thermal conductive filler;
[0070] Putting a vinyl-terminated polydimethylsiloxane having a viscosity of 1900-2100 mPa·s and a vinyl content of 0.2-0.24 wt% and a methyl-terminated methylhydrogensilane having a hydrogen content of 0.04-0.06 wt% into a distillation tower respectively, and performing distillation at a high temperature of 180° C. for 2 hours to obtain a low-vinyl-terminated polydimethylsiloxane and a low-methyl-terminated methylhydrogensilane;
[0071] By weight, 4.3 parts of de-low-end vinyl polydimethylsiloxane, 0.7 parts of de-low-methyl end-capped methylhydrogensilane, 1 part of 500,000 mPa·s polydimethylsiloxane, 0.1 parts of platinum catalyst, 0.2 parts of inhibitor, and 93.6 parts of modified thermal conductive filler were put into a reaction kettle, dispersed evenly with a planetary mixer (stirring rate of 20 Hz, stirring time of 2 h), and vacuum degassed after mixing (degassed time of 15 min, vacuum degassed pressure of -0.095 to -0.1 MPa) to obtain a thermal conductive colloid;
[0072] The thermal conductive colloid was put into a calender, and the corresponding thickness was set to 2 mm. After calendering, it passed through a vulcanization tunnel (the vulcanization temperature was 140° C., and the vulcanization time was 15 min). After vulcanization, a thermal conductive gasket was obtained.
[0073] Embodiment 2
[0074] A low-penetration and low-volatile thermally conductive pad, comprising the following raw materials by mass: 3.3 parts of de-low-end vinyl polydimethylsiloxane, 0.4 parts of de-low-methyl end-capped methylhydrogensilane, 1 part of 100,000 mPa·s polydimethylsiloxane, 0.1 parts of platinum catalyst, 0.2 parts of inhibitor, and 96 parts of modified thermally conductive filler;
[0075] The modified thermal conductive filler includes the following raw materials by mass: 45 parts of 100 μm spherical alumina, 10 parts of 90 μm aluminum nitride, 15 parts of 45 μm spherical alumina, 25 parts of 5 μm spherical alumina, 4.5 parts of 1 μm zinc oxide, 0.2 parts of dodecyl triethoxysiloxane, 0.2 parts of single-end trimethoxysilane-terminated polydimethylsilicone oil, and 0.1 parts of octadecyl trimethoxysilane;
[0076] The low-end vinyl-free polydimethylsiloxane and the low-end methyl-free methyl-terminated methylhydrogensilane are purified at 180°C from vinyl-terminated polydimethylsiloxane with a viscosity of 950-1100 mPa·s and a vinyl content of 0.3-0.34 wt% and methyl-terminated methylhydrogensilane with a hydrogen content of 0.04-0.06 wt%.
[0077] The preparation method of the thermally conductive pad comprises:
[0078] By mass, 45 parts of 100 μm spherical alumina, 10 parts of 90 μm aluminum nitride, 15 parts of 45 μm spherical alumina, 25 parts of 5 μm spherical alumina, and 4.5 parts of 1 μm zinc oxide were put into a high-speed mixer for mixing (the equipment speed was 10 Hz, and the time was 1 min), 0.2 parts of dodecyl trimethoxysiloxane and 0.3 parts of single-end trimethoxysilane-terminated polydimethylsilicone were added as a treatment agent, and then dispersed and mixed at a high speed (the equipment speed was 25 Hz, and the time was 5 min) to obtain a modified thermal conductive filler;
[0079] Putting a vinyl-terminated polydimethylsiloxane having a viscosity of 950-1100 mPa·s and a vinyl content of 0.3-0.34 wt% and a methyl-terminated methylhydrogensilane having a hydrogen content of 0.04-0.06 wt% into a distillation tower respectively, and performing distillation at a high temperature of 180° C. for 2 hours to obtain a low-vinyl-terminated polydimethylsiloxane and a low-methyl-terminated methylhydrogensilane;
[0080] By weight, 3.3 parts of de-low-end vinyl polydimethylsiloxane, 0.4 parts of de-low-methyl end-capped methylhydrogensilane, 1 part of 100,000 mPa·s polydimethylsiloxane, 0.1 parts of platinum catalyst, 0.2 parts of inhibitor, and 96 parts of modified thermal conductive filler were put into a reaction kettle, and dispersed evenly with a planetary mixer (stirring rate of 25 Hz, stirring time of 2 h), and vacuum degassed after mixing (degassed time of 20 min, vacuum degassed pressure of -0.095 to -0.1 MPa) to obtain a thermal conductive colloid;
[0081] The thermal conductive colloid was put into a calender, and the corresponding thickness was set to 2 mm. After calendering, it passed through a vulcanization tunnel (the vulcanization temperature was 140° C., and the vulcanization time was 15 min). After vulcanization, a thermal conductive gasket was obtained.
[0082] Embodiment 3
[0083] A low-penetration and low-volatility thermally conductive pad, comprising the following raw materials by weight: 4.6 parts of low-end vinyl-free polydimethylsiloxane, 0.3 parts of low-end methyl-free end-capped methylhydrogensilane, 0.8 parts of 100,000 mPa·s polydimethylsiloxane, 0.1 parts of platinum catalyst, 0.2 parts of inhibitor, and 94 parts of modified thermally conductive filler;
[0084] The modified thermal conductive filler includes, by mass, 40 parts of 80 μm aluminum nitride, 15 parts of 30 μm spherical aluminum oxide, 30 parts of 5 μm spherical aluminum oxide, 14.5 parts of 1 μm quasi-spherical aluminum oxide, 2 parts of dodecyl triethoxysiloxane, 0.2 parts of dodecyl trimethoxysiloxane, and 0.1 parts of octadecyl trimethoxysiloxane;
[0085] The low-end vinyl-free polydimethylsiloxane and the low-end methyl-free methyl-terminated methylhydrogensilane are purified at 180°C from vinyl-terminated polydimethylsiloxane with a viscosity of 450-550 mPa·s and a vinyl content of 0.4-0.45 wt% and methyl-terminated methylhydrogensilane with a hydrogen content of 0.09-0.11 wt%.
[0086] The preparation method of the thermally conductive pad comprises:
[0087] By mass, 40 parts of 80 μm aluminum nitride, 15 parts of 30 μm spherical alumina, 30 parts of 5 μm spherical alumina, and 14.5 parts of 1 μm quasi-spherical alumina were put into a high-speed mixer for mixing (the equipment speed was 10 Hz and the time was 1 min), and 2 parts of dodecyl triethoxysiloxane, 0.2 parts of dodecyl trimethoxysiloxane, and 0.1 parts of octadecyl trimethoxy were added as treatment agents, and then dispersed and mixed at a high speed (the equipment speed was 25 Hz and the time was 5 min) to obtain a modified thermal conductive filler;
[0088] Putting a vinyl-terminated polydimethylsiloxane having a viscosity of 450-550 mPa·s and a vinyl content of 0.4-0.45 wt% and a methyl-terminated methylhydrogensilane having a hydrogen content of 0.09-0.11 wt% into a distillation tower respectively, and performing distillation at a high temperature of 180° C. for 2 hours to obtain a low-vinyl-terminated polydimethylsiloxane and a low-methyl-terminated methylhydrogensilane;
[0089] By weight, 4.6 parts of de-low-end vinyl polydimethylsiloxane, 0.3 parts of de-low-methyl end-capped methylhydrogensilane, 0.8 parts of 100,000 mPa·s polydimethylsiloxane, 0.1 parts of platinum catalyst, 0.2 parts of inhibitor, and 94 parts of modified thermal conductive filler were put into a reaction kettle, dispersed evenly with a planetary mixer (stirring rate of 25 Hz, stirring time of 2 h), and vacuum degassed after mixing (degassed time of 20 min, vacuum degassed pressure of -0.095 to -0.1 MPa) to obtain a thermal conductive colloid;
[0090] The thermal conductive colloid was put into a calender, and the corresponding thickness was set to 2 mm. After calendering, it passed through a vulcanization tunnel (the vulcanization temperature was 140° C., and the vulcanization time was 15 min). After vulcanization, a thermal conductive gasket was obtained.
[0091] Comparative Example 1
[0092] A thermally conductive gasket comprises the following raw materials by weight: 4.5 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 450-550 mPa·s and a vinyl content of 0.4-0.45 wt%, 0.5 parts of methyl-terminated methylhydrogensilane with a hydrogen content of 0.09-0.11 wt%, 0.1 parts of a platinum catalyst, 0.2 parts of an inhibitor, and 94.7 parts of a modified thermally conductive filler;
[0093] The modified thermal conductive filler includes the following raw materials by mass: 40 parts of 70 μm spherical alumina, 10 parts of 40 μm alumina, 35 parts of 5 μm spherical alumina, 10 parts of 3 μm quasi-spherical alumina, 4.5 parts of 1 μm zinc oxide, 0.2 parts of dodecyl trimethoxysiloxane, and 0.3 parts of single-end trimethoxysilane-terminated polydimethylsilicone oil;
[0094] The preparation method of the thermally conductive pad comprises:
[0095] By mass, 40 parts of 70 μm spherical alumina, 10 parts of 40 μm alumina, 35 parts of 5 μm spherical alumina, 10 parts of 3 μm quasi-spherical alumina, and 4.5 parts of 1 μm zinc oxide were put into a high-speed mixer for mixing (the equipment speed was 10 Hz, and the time was 1 min), 0.2 parts of dodecyl trimethoxysiloxane and 0.3 parts of single-end trimethoxysilane-terminated polydimethylsilicone were added, and then dispersed and mixed at a high speed (the equipment speed was 25 Hz, and the time was 5 min) to obtain a modified thermal conductive filler;
[0096] By weight, 4.5 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 450-550 mPa·s and a vinyl content of 0.4-0.45 wt%, 0.5 parts of methyl-terminated methylhydrogensilane with a hydrogen content of 0.09-0.11 wt%, 0.1 parts of a platinum catalyst, 0.2 parts of an inhibitor, and 94.7 parts of a modified thermally conductive filler are added into a reaction kettle, and dispersed evenly with a planetary mixer (stirring rate of 20 Hz, stirring time of 2 h), and vacuum degassed after mixing (degassed time of 15 min, vacuum degassed pressure of -0.095 to -0.1 MPa) to obtain a thermally conductive colloid;
[0097] The thermal conductive colloid was put into a calender, and the corresponding thickness was set to 2 mm. After calendering, it passed through a vulcanization tunnel (the vulcanization temperature was 140° C., and the vulcanization time was 15 min). After vulcanization, a thermal conductive gasket was obtained.
[0098] The thermal conductivity, oil seepage diameter and siloxane content of Examples 1-3 and Comparative Example 1 were tested respectively. The oil seepage diameter was tested by preparing a 2m thick thermally conductive gasket material, cutting it to a 26mm diameter circle, placing the sample on filter paper (medium speed), and then using a jig to compress the thermally conductive gasket by 25% to a 30mm diameter circle. The jig and the gasket were placed in a 125°C oven and baked for 48 hours. The degree of gasket oil seepage was determined by calculating the oil seepage diameter. The results are shown in Tables 1 and Figure 4 As shown:
[0099] Table 1 Test results of thermal conductivity, oil seepage diameter and siloxane content of Examples 1-3 and Comparative Example 1
[0100]
[0101] In summary, the embodiments provided in the present application solve the problems of silane volatilization and silicone oil leakage during use of the thermally conductive gasket while ensuring excellent thermal conductivity, thereby enhancing the durability and stability of the product while ensuring high thermal conductivity.
[0102] The above embodiments are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to in detail.
[0103] Although the preferred embodiments of the present application have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the interpretation of the attached claims includes the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present application.
[0104] Finally, it should be noted that in this specification, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or terminal device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or terminal device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the presence of other identical elements in the process, method, article or terminal device including the elements.
[0105] The above is a detailed introduction to a low-permeability, low-volatile thermal pad and its preparation method provided by the present application. The present specification uses specific examples to illustrate the principles and implementation methods of the present application. The above examples are only used to help understand the method and its core idea of the present application. At the same time, for those skilled in the art, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present application.
Claims
1. A low-penetration and low-volatility thermally conductive pad, characterized in that: The following raw materials are included by mass: 2-8 parts of low-end vinyl-free polydimethylsiloxane, 0.1-3 parts of low-end methyl-free methyl hydrogen siloxane, 1-5 parts of polydimethylsiloxane, 90-96 parts of modified thermal conductive filler, 0.1-1 parts of platinum catalyst and 0.1-1 parts of inhibitor; The low-end vinyl-free polydimethylsiloxane and the low-end methyl-free terminated methylhydrogensilane are obtained by distillation and purification of vinyl-terminated polydimethylsiloxane and methyl-terminated methylhydrogensilane, respectively; the viscosity of the vinyl-terminated polydimethylsiloxane is 450-2100 mPa·s, and the vinyl content is 0.2-0.45 wt %; the hydrogen content of the methyl-terminated methylhydrogensiloxane is 0.04-0.15 wt %; and the viscosity of the methyl silicone oil is 100000-500000 mPa·s.
2. The thermally conductive pad according to claim 1, characterized in that: The content of small molecule substances in the low-end vinyl-free polydimethylsiloxane is less than 0.1wt%; wherein the molecular weight of the small molecule substances is less than 500Da.
3. The thermally conductive pad according to claim 1, characterized in that: The content of small molecule substances in the de-low-methyl terminated methyl hydrogen siloxane is less than 0.1 wt %; wherein the molecular weight of the small molecule substances is less than 500 Da.
4. The thermally conductive pad according to claim 1, characterized in that: The modified thermally conductive filler comprises the following raw materials by weight: 98-99.8 parts of thermally conductive filler and 0.2-2 parts of treating agent.
5. The thermally conductive pad according to claim 4, characterized in that: The thermally conductive filler includes at least one of aluminum oxide, aluminum nitride, aluminum hydroxide, zinc oxide and diamond.
6. The thermally conductive pad according to claim 4, characterized in that: The treating agent includes at least one of y-(2,3-epoxypropoxy)propyltrimethoxysilane, y-methacryloxypropyltrimethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, single-end trimethyl / ethoxysilane-terminated polydimethylsiloxane and polyether-modified polydimethylsiloxane.
7. The thermally conductive pad according to claim 6, characterized in that: The treating agent includes at least one of y-(2,3-epoxypropoxy)propyltrimethoxysilane, y-methacryloxypropyltrimethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, and at least one of single-end trimethyl / ethoxysilane-terminated polydimethylsiloxane and polyether-modified polydimethylsiloxane.
8. A method for preparing a thermally conductive gasket according to any one of claims 1 to 7, characterized in that: include: The modified thermal conductive filler, the low-end vinyl-free polydimethylsiloxane, the low-end methyl-free methyl hydrogen siloxane, the polydimethylsiloxane, the platinum catalyst and the inhibitor are mixed and stirred according to the proportion, and vacuum degassing treatment is performed to obtain a thermal conductive colloid; The thermally conductive colloid is subjected to calendering and vulcanization treatment to obtain a thermally conductive gasket.
9. The preparation method according to claim 8, characterized in that: Also includes: The thermal conductive filler and the treating agent are stirred and mixed according to a proportion to obtain a modified thermal conductive filler.
10. The preparation method according to claim 8, characterized in that: Also includes: The vinyl-terminated polydimethylsiloxane and the methyl-terminated methylhydrogensiloxane were distilled at 180° C. for 2 h to obtain the low-vinyl-terminated polydimethylsiloxane and the low-methyl-terminated methylhydrogensiloxane.